Study of aerobic bacterial conjunctival flora in patients with diabetes mellitus - Karimsab, D; Razak, SK (Nepalese Journal of Ophthalmology, 2013)
Introduction: Normal bacterial flora may be altered by a variety of factors. Objective: To study the aerobic bacterial conjunctival flora in patients with diabetes mellitus and to find its clinical significance by comparing the results to the conjunctival flora of non-diabetic subjects. Materials and methods: A total of 75 diabetic patients were included as cases and 25 nondiabetics as controls to compare the results. Specimens for the study of conjunctival flora were taken by rubbing sterile cotton-tipped swabs to the inferior palbebral conjunctiva. The conjunctival culture report of the patients with diabetic mellitus was compared to that of nondiabetic subjects. Results: Positive conjunctival cultures were seen in a higher percentage of patients with diabetes (unilateral and bilateral positive conjunctival cultures 34.66 % and 58.66 % respectively) compared to that in non-diabetic controls (unilateral and bilateral positive conjunctival cultures 24 % and 16 % respectively). Diabetics showed a higher proportion of coagulase negative staphylococci (45.33 %), compared to the non-diabetic group (16 %). Among the diabetic patients, positive conjunctival cultures were detected more frequently in those with diabetic retinopathy compared to those without retinopathy. A higher proportions of bilateral positive conjunctival cultures were seen in cases with proliferative diabetic retinopathy (38.63 %) in comparison to patients with no retinopathy and different stages of non-proliferative diabetic retinopathy. Conclusion: The conjunctival floral pattern with increased bacteria in diabetics is a predominant cause of many diabetes-related ocular infections. The presence of diabetic retinopathy is an indicator for increased colonization of conjunctiva, and its severity correlates with the severity of diabetic retinopathy. Nepal J Ophthalmol 2013; 5(9):28-32 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7818